A comparison of artificial neural networks and multiple regression methods for the analysis of pilot-scale data. (1st April 2004) - Stanley, Stephen J; Smith, Daniel W; Baxter, C W
Abstract : Pilot-scale testing is widely used in the drinking water supply industry to test treatment theories, develop new processes, and enhance process operations. The data sets derived from pilot testing are usually small owing to financial and time considerations. The analysis of such data is extremely complex, since treatment processes are highly complex and nonlinear. Multiple regression analysis is widely considered to be the best available technology for analysing data collected from pilot-scale experiments in the drinking water supply industry. Unfortunately, this technique is limited in its ability to handle the combinations of fixed and random variables that are characteristic of water treatment processes. This paper demonstrates the applicability and advantages of artificial network modelling for pilot-scale data analysis. Data collected at two separate pilot-scale facilities are analysed using the artificial neural network (ANN) technique and multiple regression methods, and performance assessments of the two are made.